Volunteered and crowdsourced geographic information: the OpenStreetMap project - Michela Bertolotto; Gavin McArdle; Bianca Schoen-Phelan (Journal of Spatial Information Science, 2020)
Advancements in technology over the last two decades have changed how spatial data are created and used. In particular, in the last decade, volunteered geographic information (VGI), i.e., the crowdsourcing of geographic information, has revolutionized the spatial domain by shifting the map-making process from the hands of experts to those of any willing contributor. Started in 2004, OpenStreetMap (OSM) is the pinnacle of VGI due to the large number of volunteers involved and the volume of spatial data generated. While the original objective of OSM was to create a free map of the world, its uses have shown how the potential of such an initiative goes well beyond map-making: ranging from projects such as the Humanitarian OpenStreetMap (HOT) project, that understands itself as a bridge between the OSM community and humanitarian responders, to collaborative projects such as Mapillary, where citizens take street-level images and the system aims to automate mapping. A common trend among these projects using OSM is the fact that the community dynamic tends to create spin-off projects. Currently, we see a drive towards projects that support sustainability goals using OSM. We discuss some such applications and highlight challenges posed by this new paradigm. We also explore the most promising future uses of this increasingly popular participatory phenomenon.